Strengthening Rödl's theorem - Chudnovsky, M; Scott, A; Seymour, P; Spirkl, S (Elsevier, 2023)
What can be said about the structure of graphs that do not contain an induced copy of some graph H? Rödl showed in the 1980s that every H-free graph has large parts that are very sparse or very dense. More precisely, let us say that a graph F on n vertices is ε-restricted if either F or its complement has maximum degree at most εn. Rödl proved that for every graph H, and every ε > 0, every H-free graph G has a linear-sized set of vertices inducing an ε-restricted graph. We strengthen Rödl’s result as follows: for every graph H, and all ε > 0, every H-free graph can be partitioned into a bounded number of subsets inducing ε-restricted graphs.